2016
DOI: 10.1016/j.molonc.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPER suppresses epithelial mesenchymal transition of triple negative breast cancer cells via NF‐κB signals

Abstract: The targeted therapy for triple-negative breast cancer (TNBC) is a great challenge due to our poor understanding on its molecular etiology. In the present study, our clinical data showed that the expression of G-protein coupled estrogen receptor (GPER) is negatively associated with lymph node metastasis, high-grade tumor and fibronectin (FN) expression while positively associated with the favorable outcome in 135 TNBC patients. In our experimental studies, both the in vitro migration and invasion of TNBC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 57 publications
6
70
0
2
Order By: Relevance
“…Further in vitro researches illustrated that activation of GPER through G-1 attenuated DHT–induced proliferation. Coincidentally, our current data are consistent with another study indicating that G-1 inhibited the in vivo growth and invasive potential of TNBC [43]. Consistent to the in vitro studies, the negative correlation of AR and GPER was confirmed in patient tissues and nude mouse xenografts.…”
Section: Discussionsupporting
confidence: 92%
“…Further in vitro researches illustrated that activation of GPER through G-1 attenuated DHT–induced proliferation. Coincidentally, our current data are consistent with another study indicating that G-1 inhibited the in vivo growth and invasive potential of TNBC [43]. Consistent to the in vitro studies, the negative correlation of AR and GPER was confirmed in patient tissues and nude mouse xenografts.…”
Section: Discussionsupporting
confidence: 92%
“…Others linked GPER with a better OS and DFS, and in a further study on invasive breast cancer, GPER expression was more common in smaller tumours . In triple‐negative breast cancer, GPER expression was positively correlated with a favourable patient outcome, and negatively with high tumour grade and lymph node metastasis, an effect most likely mediated by inhibition of epithelial mesenchymal transition . Based on novel observations new, GPER‐targeted therapies are in pipeline to better target triple‐negative breast cancer .…”
Section: Discussionmentioning
confidence: 96%
“…[58][59][60] In triple-negative breast cancer, GPER expression was positively correlated with a favourable patient outcome, and negatively with high tumour grade and lymph node metastasis, an effect most likely mediated by inhibition of epithelial mesenchymal transition. 61 Based on novel observations new, GPER-targeted therapies are in pipeline to better target triple-negative breast cancer. [62][63][64] In seminomas and in situ testicular carcinomas, the down regulation of ERb expression together with GPER overexpression conferred oestrogen responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform a detailed analysis to clarify the cell proliferation effect of GPER on macrophages, GPER has been suggested to negatively regulate inflammatory cytokine expression pathways (and not affect cell proliferation). Furthermore, GPER suppresses epithelial mesenchymal transition, migration and angiogenesis of triple negative breast cancer cells via inhibition of the NF-jB signal (Chen et al 2016;Liang et al 2017). S2).…”
Section: Discussionmentioning
confidence: 99%